Rekonstruksi fungsi pencegahan terjadinya tindak pidana korupsiPada bank badan usaha milik negara (bumn) - Te’dang, Yonika Winner; Nainggolan, Marsudin; Kristiawanto, Kristiawanto (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The function of preventing corruption crimes at SOE Banks has not been maximized so far. This is due to the lack of supervision and accountability carried out by the SOE Bank, which causes corruption crimes committed by the SOE Bank officers. The research method used by the researcher uses a qualitative research method where the data will be analyzed descriptively to explain the existing data and associate one data with another. The results of the existing research explain that so far the function of preventing corruption at SOE Banks is still not optimal because the implementation of supervision and accountability has not been carried out properly by the SOE Bank officers. As a result of the lack of a function to prevent criminal acts through supervision and accountability, it is very vulnerable to corruption crimes as has happened at Bank BRI Yos Sudarso Branch Office, Palangka Raya. The occurrence of corruption crimes committed by BRI Staff of Yos Sudarso Branch Office resulted in state losses so that the perpetrators must be given criminal penalties as stipulated in the Law on the Eradication of Corruption Crimes. Therefore, it is important to establish a reconstruction of the function of preventing corruption crimes at SOE Banks in the form of maximizing the implementation of supervision and accountability by the officers of the SOE Bank. By maximizing supervision and accountability, the prevention function can be carried out and corruption crimes in state-owned banks can be prevented and minimized